Legal Implications of the Articles of Association in Foundation Governance - Putra, Tria Sasangka; Akbar, Bahrullah (Unissula, 2024)
Foundations play a significant role in supporting social missions, and understanding their legal obligations, as stated in the Articles of Association, is essential to ensuring their sustainability. This research examines the legal framework governing foundations in Indonesia, specifically focusing on Law Number 28 of 2004, which outlines the requirements for foundation establishment and operation. The study uses a qualitative, normative juridical approach to analyze the legal implications of mismanagement in foundation operations that deviate from the Articles of Association. The research highlights how non-compliance with these guidelines—especially the Articles of Association—along with the failure to submit financial reports and adhere to governance standards, can lead to serious legal and socio-economic consequences. The findings emphasize that mismanagement can damage a foundation’s credibility, cause internal conflicts, and result in legal claims from stakeholders. The study also explores the importance of effective government oversight, particularly by the Ministry of Law, in ensuring foundations comply with legal regulations. To address violations, the research suggests several approaches, including internal resolutions, legal reporting, and stronger supervision. Its further advocates for increased legal awareness and training for foundation managers to prevent violations and safeguard the foundation's integrity.